Catálise heterogênea utilizando íons cobre para a obtenção de compostos N-heterocíclicos - Sousa, Bruno Kaleb dos Santos Pinto de (Universidade Federal de São Carlos, 2023)
N-Heterocyclic compounds, such as pyrroloquinazolines, are widely used in the agrochemical and pharmaceutical industries due to their broad spectrum of biological activity and relative low toxicity. Synthetic methods for these compounds have been explored, including those based on zeolites as heterogeneous catalysts, aiming to overcome challenges associated with homogeneous catalysis, such as the difficulty in separating the catalyst from the reaction medium. In this context, this work provides a review of the structure, synthesis, and various applications of quinazolines. Pyrroloquinazolines, in specific, have been the subject of studies, including their antiparasitic properties. The study also explores recent methods for the formation of these compounds, focusing on the use of zeolites as heterogeneous catalysts. Specifically, the formation of pyrroloquinazoline using various zeolites was investigated. Characterization and recycling of the USY zeolite were key aspects of the analysis, with observed yields of 73% during catalyst screening and variations between 68 and 56% over 4 reaction cycles. The work concludes with the perspective of continuous optimization of the reaction for better yields and exploration of the synthesis of new derivatives, demonstrating the viability and efficacy of heterogeneous catalysis in this context.
Heterogeneous catalysis using copper ions on the synthesis N-heterocyclic compounds
Keywords: Química Verde; Catálise heterogênea; Zeólitas; Compostos N-heterocíclicos; Quinazolina; Pirroloquinazolina; Síntese orgânica; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA